Frasa Mubālaghah “ظلوم Dan جهول” Dalam Al-Qur'an: Studi Analisis Morfologis Semantik - Busyro, Ahmad; Taufiq, Wildan (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This research examines the mubālaghah phrases "ظلوم and جهول" in the Quran and aims to conduct morphological and semantic analysis on this pattern in the Quran. The researcher uses a method of morphological and semantic analysis to analyze the use of the phrases "ظلوم and جهول" in the Quran and to reveal its linguistic and contextual significance. The findings of this research conclude that the forms "ظلوم and جهول" appear only once in the Quran, in Surah Al-Ahzab, verse 72, where Allah says: "إِنَّهُ كَانَ ظَلُوْمًا جَهُولًا" ("Indeed, he was unjust and ignorant"). The use of this form in the mentioned verse indicates several meanings: first, etymologically, this mubālaghah phrase expresses an exaggerated meaning in describing human attributes "ظالم and جاهل," meaning oppressive and ignorant; second, ظالم means oppressing oneself, and جاهل means being ignorant and negligent of God's commands; third, "ظالم" means oppressing oneself, and "جاهل" means neglecting the consequences of one's actions; fourth, "ظالم" oppressing oneself is accompanied by disobedience to God, and "جاهل" means being foolish by disregarding the punishment for disobedience. Based on these results, it can be concluded that the use of this form helps in understanding the precise meanings of words in the Quran.